2020
DOI: 10.1002/jrs.6047
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in benzene under dynamic and static compression

Abstract: Phase transitions in liquid benzene under laser shocked conditions are studied using high‐resolution time‐resolved Raman spectroscopic technique. The C‐C ring breathing mode (υ1) of benzene at 993 cm−1 is analyzed to monitor the phase transitions occurring in the Raman spectra during shock wave propagation in the pressure range 1.3–5 GPa. Phase transition from liquid benzene to solid benzene (Phase I) is observed below 1.3 GPa, and above this pressure, another phase transition from Phases I and II occurs. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…[2][3][4] Among others, the high-pressure behavior of C 6 H 6 has always been a research hotspot, from P. W. Bridgman's classic pioneering study to the present. 5,6 The pressure can change the physical form and lattice structure of C 6 H 6 and lead to a series of phase transitions. Previous Raman and X-ray studies indicated that C 6 H 6 transformed from a liquid crystal phase to a solidified phase I (Pbca) with an orthorhombic structure at 0.07 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Among others, the high-pressure behavior of C 6 H 6 has always been a research hotspot, from P. W. Bridgman's classic pioneering study to the present. 5,6 The pressure can change the physical form and lattice structure of C 6 H 6 and lead to a series of phase transitions. Previous Raman and X-ray studies indicated that C 6 H 6 transformed from a liquid crystal phase to a solidified phase I (Pbca) with an orthorhombic structure at 0.07 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…2–4 Among others, the high-pressure behavior of C 6 H 6 has always been a research hotspot, from P. W. Bridgman's classic pioneering study to the present. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the P-T phase diagram has been constructed to determine the solid, liquid and gaseous states for benzene [32]. Phase transitions in liquid benzene (solid-liquid transition) has been studied by using high-resolution time-resolved Raman spectroscopic technique [33].…”
Section: Introductionmentioning
confidence: 99%
“…The technique has allowed researchers to better understand how lasers interact with matter-and how shock-/pressure-waves travel through materials at high pressures [27,29]. Although multi-stage DACs can achieve pressures greater than 380 GPa, when sample sizes greater than 20 µm across are to be compressed, the LDC-DAC mode is presently the primary means to achieve pressures >> 380 GPa [19,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%